The Effects of Local Application of Ankaferd Blood Stopper on Bone Regeneration of Defects in Rat Tibias - Özcan, Erhan Cahit; Tanrısever, Murat; Bal, Ali; Karasu, Necmettin; Bozoglan, Alihan; Artaş, Gökhan; Dündar, Serkan (My University, 2025)
Objective: Ankaferd Blood Stopper (ABS) is a historical hemostatic material that is a mixture of five medicinal plant extracts. The local application of ABS is believed to increase bone healing due to its anti-inflammatory and antioxidant capacity. In this experimental study of rats, the effects of local ABS on bone healing in a tibia defect model were examined histopathologically. Materials and Methods: Sixty female Sprague-Dawley rats were randomly divided into two groups of 30 animals each. One cylindrical bone defect with a diameter of 4 mm and a depth of 4 mm was created in the right tibia of each rat under general anesthesia. As much ABS as the defect could take was applied locally in the rats in the experimental group. No additional procedure was applied in the controls. At 2, 4, and 8 weeks postoperative, the rats were sacrificed with carbon dioxide ventilation, and bone samples were taken from their right tibias. The samples were evaluated histopathologically for fibrosis and new bone formation. Results: The results showed that ABS application did not increase the regeneration of bone tissue in the defect areas during the bone healing period, although this was not statistically significant (p>0.05). No statistically significant difference was observed between the control and ABS groups in terms of fibrosis (p>0.05). Conclusion: This herbal product may not have positive effects on bone tissue healing when used locally. Further studies are needed to evaluate the possible benefits and side effects of ABS on bone tissue.
Keywords: Bone healing; Ankaferd blood stopper; herbal medicines; bone regeneration; local application